Multiscale analysis of T cell activation: Correlating in vitro and in vivo analysis of the immunological synapse - Dustin, M (2009)
Recently implemented fluorescence imaging techniques, such as total internal reflection fluorescence microscopy and two-photon laser scanning micro-scopy, have made possible multiscale analysis of the immune response from single molecules in an interface to cells moving in lymphoid tissues and tumors. In this review, we consider components of T cell sensitivity: the immunological synapse, the coordination of migration, and antigen recognition in vivo. Potency, dose, and detection threshold for peptide-MHC determine T cell sensitivity. The immunological synapse incorporates T cell receptor microclusters that initiate and sustain signaling, and it also determines the positional stability of the T cells through symmetry and symmetry breaking. In vivo decisions by T cells on stopping or migration are based of antigen stop signals and environmental go signals that can sometimes prevent arrest of T cells altogether, and thus can change the outcome of antigen encounters. © 2010 Springer-Verlag Berlin Heidelberg.